Cubics 2
 Identify the correct equation for each graphFunction: Cubic 2-24-42-24-46-6y=(x-1)2(x+2)y=(x+1)2(x-2)y=(x-2)2(x+1)y=(x+2)2(x-1) 2-24-42-24-46-6y=(x-1)2(2-x)y=(x+1)2(2-x)y=(2-x)2(x+1)y=(x+2)2(1-x) 2-22-24-4y=(x-1)(x-0)(x+2)y=(1-x)(x-0)(2+x)y=(x-2)(1+x)xy=(2-x)(1+x)x 2-24-46-62-24-46-68-810-10y=(x-3)2(x+2)y=1/2(x+3)2(x-2)y=1/3(x+3)2(x-2)y=1/3(x-3)2(x+2) 1-12-21-12-23-3y=(x-1)(x+2)(x-2)y=(x+1)(x+2)(x-2)y=-(x+1)(x+2)(x-2)y=-(x-1)(x+2)(x-2) 1-12-21-12-23-3y=(x-1)(x+2)(x-2)y=(x+1)(x+2)(x-2)y=-(x-1)(x+2)(x-2)y=-(x+1)(x+2)(x-2) 2-24-46-62-24-46-68-810-10y=2(x-1)(x+1)(x-3)y=(x-1)(x+1)(x-3)y=-2(x-1)(x+1)(x-3)y=-(x-1)(x+1)(x-3) 2-24-46-62-24-46-68-810-10y=2(x-1)(x+1)(x-3)y=(x-1)(x+1)(x-3)y=-(x-1)(x+1)(x-3)y=-2(x-1)(x+1)(x-3) 2-24-46-62-24-46-68-810-10y=2(x)(x-2)(x-4)y=-(x)(x-2)(x-4)y=-2(x)(x-2)(x-4)y=(x)(x-2)(x-4) 2-24-46-62-24-46-68-810-10y=2(x+3)(x-2)(x+2)y=1/2(x+3)(x-2)(x+2)y=1/2(x+3)(x-3)(x+2)y=2(x+3)(x-3)(x+2)
Students who took this test also took :

Created with That Quiz — where a math practice test is always one click away.